Labor Informality and Economic Political Accountability of Executive Incumbents in Latin America - Acevedo-Pardo, Julián (Revista Latinoamericana de Opinión Pública, 2021)
Many governments across Latin America have been unable to reduce stubbornly high levels of labor informality and the lack of legal and social protection has put informal workers in a situation of continuous economic peril and uncertainty. This paper argues that the inherent characteristics and conditions of informal workers act as noisy signals that diminish the effect that economic perceptions have on evaluations of the incumbent executive across Latin American countries. The empirical results support the argument, suggesting that the effect of perceptions of the economy on evaluations of the incumbent is lower among informal relative to formal workers. Furthermore, this dynamic is prevalent in urban areas where there is a more evident differentiation between formal and informal workers, and disappears in rural areas, where both formal and informal workers face challenges that produce noisy signals and diminish the effect of perceptions of the economy on evaluations of the incumbent.